Development of a Neuropsychological Questionnaire for Marital Conflicts and Examination of Its Psychometric Properties in Iran - Nasr Esfahani, Malihe; Tamadoni, Mojtaba; Sedaghat, Mastooreh (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The aim of the present study was to develop a neuropsychological questionnaire for marital conflicts and to examine its psychometric properties in Iran.Methods and Materials: This study was conducted in two phases: pilot and final. In the pilot phase, the initial questionnaire was administered to 81 couples experiencing marital conflict, and its structure was examined using exploratory factor analysis. In the final phase, the revised version was administered to 318 couples with marital conflict and 112 married individuals without severe conflict. To assess convergent validity, the Barati and Sanaei Marital Conflict Questionnaire and the ENRICH Marital Satisfaction Questionnaire were used. Data analysis was conducted using reliability indices, construct validity, convergent and discriminant validity, and confirmatory factor analysis.Findings: The results indicated that the questionnaire has a five-factor structure including the prefrontal cortex, anterior cingulate gyrus, deep limbic system, basal ganglia, and temporal cortex. Correlation coefficients with the marital conflict scale ranged from 0.58 to 0.62, and correlations with marital satisfaction were negative and significant. Additionally, significant differences were observed between couples with and without conflict across all components (p < 0.01).Conclusion: The neuropsychological marital conflict questionnaire demonstrated satisfactory validity and reliability and can be used as a culturally adapted and valid instrument for assessing the neuropsychological dimensions of marital conflicts in research and clinical interventions.